Exploiting hiPSCs in Leber's Hereditary Optic Neuropathy (LHON): Present Achievements and Future Perspectives - Peron, Camille; Maresca, Alessandra; Cavaliere, Andrea; Iannielli, Angelo; Broccoli, Vania; Carelli, Valerio; Di Meo, Ivano; Tiranti, Valeria (Frontiers in Neurology, 2021)
More than thirty years after discovering Leber’s hereditary optic neuropathy (LHON) as the first maternally inherited disease associated with homoplasmic mtDNA mutations, we still struggle to achieve effective therapies. LHON is characterized by selective degeneration of retinal ganglion cells (RGCs) and is the most frequent mitochondrial disease, which leads to blindness young people, in particular males. Despite the causative mutations are present in all tissues, yet only a specific cell type is affected. Our deep understanding of the pathogenic mechanisms in LHON is hampered by the lack of appropriate models since investigations have been traditionally performed in non-neuronal cells. Effective in vitro models of LHON are now emerging, casting promise to speed our understanding of pathophysiology and test therapeutic strategies to accelerate translation into clinic. We here review the potentials of these new models and their impact on the future of LHON patients.